PENENTUAN KEMIRINGAN SUDUT OPTIMAL PANEL SURYA - T. M. Aziz Pandria; Mukhlizar Mukhlizar (Universitas Teuku Umar, 2017)
This paper discusses the determination of the optimal tilt angle of solar panels in the Nagan Raya aims to maximize acceptance of solar radiation. Adjust the titl angle customized panels with latitude location can maximize the acceptance of solar radiation. Calculation of the optimal angle variations is simulated at an angle of 10 – 50 intervals between angle 10. For the purposes of simulation calculation of optimal tilt angle against the value-based maximum radiation on tilted surface, use data that NASA SEE. A study conducted in Nagan Raya this is determined based on the google maps coordinates of the point. This research resulted in recommendations for the optimum tilt angle in Nagan Raya who was the tilt 40 with South-facing orientation. The results of the technical study of this research can be used as initial references against the installation of a solar panel fixed type in the Nagan Raya.Keywords: Optimum angle, Solar panels, NASA SSE, Nagan Raya, Renewable Energy